Performance of tambacu hybrid (♂Piaractus mesopotamicus x ♀Colossoma macropomum) and its parental pacu (Piaractus mesopotamicus) evaluated in cages under different feeding programmes - Neto, Rafael Vilhena Reis [UNESP]; Hashimoto, Diogo Teruo [UNESP]; Corrêa, Camila Fernandes; Enke, Dariane Beatriz Schoffen [UNESP]; Gervaz, Washington Rocha [UNESP]; Lattanzi, Gabriel Rinaldi [UNESP] (Elsevier, 2020)
We evaluated the growth and body traits of pacu and tambacu hybrid reared in cages and fed through different feeding programmes. Six treatments in a factorial scheme, with two genetic groups (pacu and tambacu) and three feeding programmes, were tested in 12 cages. In each cage, 50 juveniles (pacu, 120 ± 31 g; tambacu, 119 ± 28 g) were stocked and fed according to three feeding programmes using three commercial diets containing 24%, 28% or 32% crude protein in different combinations during 167 days. Measurements were performed on ten animals sampled from each experimental unit at days 30, 60 and 167 of the experiment, and the weights were recorded. During the final sampling, in addition to weights, the measurements of standard length, head length, height and body width were recorded. Five of the ten animals sampled at 167 days were euthanised and processed to obtain the carcass, rib, fillet, gut and fat yields. The fillets from two of the five processed fish were used to determine the chemical composition. Data were submitted to analysis of variance and means were compared by the SNK test. The pacu group presented higher weight averages than the tambacu throughout the experiment, especially when the animals were fed by the programme with the lowest dietary protein levels. Body shape and yields were also more noteworthy for the pacu group; however, the pure animals also presented higher lipid values in the fillet, which may be a negative aspect of the final product consumed. In general, tambacu hybrid production in cages does not seem to be an interesting alternative to the farming of the pure parental species.
Keywords: body traits; chemical analysis; diets; Serrasalmidae